Performance analysis of power beacon-assisted D2D communication networks in the presence of eavesdropper and co-channel interference - Bui Vu Minh; Van-Duc Phan (Institute of Advanced Engineering and Science, 2021)
Performance analysis of power beacon-assisted D2D communication networks in the presence of eavesdropper and co-channel interference is presented is investigated. The outage probability and the intercept probability of the proposed system are analyzed and derived. The impact of the main system parameters on the system performance is investigated. The Monte Carlo simulation is used for verifying the correctness of the analytical section.